PENGARUH KEPUASAN KERJA DENGAN MEDIASI PERCEIVED ORGANIZATIONAL SUPPORT TERHADAP KOMITMEN KARYAWAN BANK - Sri Wahyu Lelly Hana Setyanti; Nira Puspitasari; Ema Desia Prajitiasari (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to determine the effect and analyze: (1) job satisfaction on employee commitment, (2) job satisfaction on Perceive Organizational Support, (3) Perceive Organizational Support on commitment, (4) job satisfaction through the mediation of Perceived Organizational Support on employee commitment. . The research approach used in this research is quantitative. The research population is employees of conventional banks in Jember Regency with a sampling technique using cluster sampling at Bank Mandiri and Bank Rakyat Indonesia (BRI) Jember with 72 respondents. The data analysis method used is path analysis. The results of testing and data analysis showed that the variable job satisfaction had a significant effect on the commitment of conventional bank employees in Jember Regency by 67.3%, job satisfaction on perceived organizational support of 73.3%, perceived organizational support on employee commitment of 80.6% and job satisfaction through the mediation of Perceived Organizational Support. to the commitment of employees of conventional banks in Jember Regency by 59.1%.